Use of aromatase inhibitors and bisphosphonates as an anticancer therapy in postmenopausal breast cancer. Issue 11 (November 2010) - Mouridsen, Henning T; Lønning, Per; Beckmann, Matthias W; Blackwell, Kimberly; Doughty, Julie; Gligorov, Joseph; Llombart-Cussac, Antonio; Robidoux, Andre; Thürlimann, Beat; Gnant, Michael
Breast cancer is a major cause of morbidity and mortality in postmenopausal women worldwide. Reducing the risk of distant disease recurrence is a primary goal of adjuvant endocrine therapy. As we await data from ongoing Phase III comparison trials, an emerging body of evidence demonstrates important differences between third-generation aromatase inhibitors, particularly with respect to potency and prevention of early distant metastases. Furthermore, a growing body of evidence demonstrates anticancer benefits of bisphosphonates in adjuvant breast cancer and other settings. This article outlines the proceedings from an Expert Panel meeting of regionally diverse breast cancer specialists regarding the appropriate use of aromatase inhibitors in postmenopausal hormone-responsive early breast cancer and bisphosphonates as anticancer therapy in adjuvant breast cancer.